PELATIHAN DESAIN PERKULIAHAN PERGURUAN TINGGI BERBASIS KOMPETENSI DOSEN DI STAI YOGYAKARTA - Assaiq, Muhammad Royhan; Agustini; Agus Suprianto; Khaerul Anwar; Hudan Mudaris (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study analyzes the effectiveness of a training program on lecture design in enhancing the pedagogical competence of lecturers at STAI Yogyakarta. Adopting a qualitative approach with a case study design, the research explores how the program successfully transforms the teaching paradigm from a conventional, teacher-centered model to an active, student-centered learning philosophy. Primary data were collected through in-depth observations and documentation involving 25 participating lecturers from STAI Yogyakarta. The data analysis utilizes content analysis and is validated through data triangulation to ensure the credibility of the findings. The results show that the training effectively shifted the lecturers' roles from being sole knowledge providers to being facilitators and mentors. A key finding is the adoption of innovative instruments like Concept Maps, which help lecturers logically organize complex subjects and integrate Islamic values into their curriculum. Furthermore, the implementation of authentic assessment ensures that learning outcomes are measured not only by memorization but also by analytical and practical skills, aligning with national educational standards. This training successfully fosters holistic competencies—covering cognitive, affective, and psychomotor domains—and provides a valuable model for other Islamic higher education institutions.